2023
DOI: 10.1038/s41598-022-25579-3
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and experimental validation to identify the potential mechanism of Hedyotis diffusa Willd against rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, autoimmune disease that may lead to joint damage, deformity, and disability, if not treated effectively. Hedyotis diffusa Willd (HDW) and its main components have been widely used to treat a variety of tumors and inflammatory diseases. The present study utilized a network pharmacology approach, microarray data analysis and molecular docking to predict the key active ingredients and mechanisms of HDW against RA. Eleven active ingredients in HDW and 180 potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…From the TF–mRNA–miRNA regulatory network we predicted, it can be seen that there are some common transcription factors (such as ESR1) and miRNAs (including hsa-miR-671-5p, hsa-miR-939-5p, hsa-miR-6752-5p, hsa-miR-6858-5p, hsa-miR-6824-5p, hsa-miR-6765-5p, and hsa-miR-6089) between FAM209B and PTGES. Among them, ESR1 was a hub gene in many autoimmune diseases ( 57 ), including type 1 diabetes ( 58 ), systemic lupus erythematosus ( 59 ), and rheumatoid arthritis ( 60 ). ESR1 was widely expressed in thymocytes, T cells, B lymphocytes, etc., which serve roles in the functioning of the immune system and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…From the TF–mRNA–miRNA regulatory network we predicted, it can be seen that there are some common transcription factors (such as ESR1) and miRNAs (including hsa-miR-671-5p, hsa-miR-939-5p, hsa-miR-6752-5p, hsa-miR-6858-5p, hsa-miR-6824-5p, hsa-miR-6765-5p, and hsa-miR-6089) between FAM209B and PTGES. Among them, ESR1 was a hub gene in many autoimmune diseases ( 57 ), including type 1 diabetes ( 58 ), systemic lupus erythematosus ( 59 ), and rheumatoid arthritis ( 60 ). ESR1 was widely expressed in thymocytes, T cells, B lymphocytes, etc., which serve roles in the functioning of the immune system and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The layout and network options were selected. From the 552 enriched pathways, eight significant KEGG pathways [ 37 ] were filtered and visually represented as a split doughnut pie chart within the network using a different color palette ( Figure 1B ) [ 38 , 39 ]. The purpose of drug–target enrichment is to unveil significant therapeutic targets, offering intricate guidance for drug discovery and development, with a special emphasis on drug–target checkpoints.…”
Section: Software and Methodsmentioning
confidence: 99%
“…Hedyotis diffusa , belongs to the Rubiaceae plant family. This plant is renowned for its anti‐inflammatory, immune regulation, and antioxidant properties (Deng et al., 2023; He et al., 2018). Recent studies have demonstrated the potential inhibitory effects of certain components of H. diffusa on enzymes associated with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%